Citizen science as a resource to define threats to bathing on beaches. The case of jellyfish in Malaga. - Cantarero-Prados, Francisco José; De-la-Fuente-Roselló, Ana Luisa (Inderscience, 2024)
This study characterises the threat due to visits by swarms of jellyfish on the coast of the province of Malaga, Spain, one of the most touristic in Spain. To achieve this objective, it uses the data collected by the Infomedusa and Medusapp applications, in addition to the historical data collected in the jellyfish layer provided by the Andalusian regional government. A geographic information system is used for the geolocation and compilation of the data provided by the three sources. The result is maps where you can see the areas of the province most exposed to the arrival of jellyfish based on recorded historical data. The information generated is very useful and could be combined with beach carrying capacity maps for better risk management due to the arrival of jellyfish in the province
Política de acceso abierto tomada de: https://www.inderscience.com/mobile/inauthors/index.php?pid=74
Keywords: Playas; Medusas - Control; Medusas; Aplicaciones; Málaga; Ciencia ciudadana